Mitochondrial and nuclear phylogenetic trees and divergence time estimations of Sulawesi endemic Adrianichthyidae - Mokodongan, Daniel F. (Data Brief, 2015)
This data article is related to the research article entitled “Origin and intra-island diversification of Sulawesi endemic Adrianichthyidae” by Mokodongan and Yamahira [1]. In this data article, we present phylogenetic trees of Sulawesi adrianichthyids separately reconstructed using mitochondrial (cytochrome b: cyt b and NADH dehydrogenase subunit 2: ND2) and nuclear (tyrosinase) sequences. We also present Bayesian chronograms of Sulawesi adrianichthyids separately estimated using a substitution rate for cyt b and for ND2.